Impact of land degradation from mining activities on the sediment fluxes in two large rivers of French Guiana. (29th October 2018) - Gallay, Marjorie; Martinez, Jean‐Michel; Allo, Sébastien; Mora, Abrahan; Cochonneau, Gérard; Gardel, Antoine; Doudou, Jean‐Claude; Sarrazin, Max; Chow‐Toun, Franck; Laraque, Alain
Abstract: We analyzed two contrasting catchments located among the world's largest unspoiled tropical rainforests impacted by mining in the northeastern coastlands of South America. We used the following: (a) mining, agricultural, and urbanized areas to compare the land use evolution with suspended sediments and sediment yields; (b) field monthly river suspended sediments in the two catchments (2004–2015: n = 154); (c) MODIS remote sensing water color technique in the Maroni basin to complete ( n = 387) and extend field suspended sediment sampling from 2000 to 2015; (d) hydroclimatic statistical analysis conditions and sediment concentrations to identify the long‐term trends, the abrupt changes in time series and to analyze if the environmental and anthropogenic factors control sediment yield regional variations. No significant long‐term changes were observed in precipitation or water discharge with the Mann–Kendall test. However, the mean suspended sediment concentration has increased significantly (239%) in the Maroni River with a breakpoint in 2009 and decreased (33%) in the Oyapock River (breakpoint in 2008). These differences are explained by the larger percentage of deforestation because of mining activities in the Maroni (0.37%) than in the Oyapock (0.06%) catchment. In the Maroni River, the increasing sediment yield trend (2000–2015) coincide significantly ( r 2 = 0.97; p < 0.0001) with the increase of 400% of mining areas, whereas no significant relationship with the runoff was found. In the Oyapock River, the runoff explains the sediment yield decreasing trend ( r 2 = 0.82; p < 0.0001) and no relationship with the land use change was found.